2004
DOI: 10.1093/intimm/dxh014
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel spliced variant that encodes human soluble tumor necrosis factor receptor 2

Abstract: Tumor necrosis factor (TNF)-alpha is a pleiotropic cytokine involved in a broad spectrum of inflammatory and immune responses including proliferation, differentiation and cell death induction in several cell types. The biological effects of TNF-alpha are mediated via the cell-surface TNF receptors TNFR1 and TNFR2. Soluble forms of these two receptors, which contain the extracellular ectodomains, are proteolytically cleaved from the membrane. High levels of soluble (s) TNFR2 in serum have been documented in mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 44 publications
1
65
0
1
Order By: Relevance
“…Several genes have been shown to produce both [85] soluble and membrane-associated protein isoforms by selective incorporation of exons encoding transmembrane regions. In particular, several tumor necrosis factor receptor (TNFR) genes are alternatively spliced in a regulated manner to produce either soluble or membrane-associated signal-transducing forms [10][11][12][13][14][15]. Xing et al [16] showed that alternative inclusion/exclusion of membrane-spanning regions is a common outcome of alternative splicing, a result that was corroborated in a mouse-specific study [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several genes have been shown to produce both [85] soluble and membrane-associated protein isoforms by selective incorporation of exons encoding transmembrane regions. In particular, several tumor necrosis factor receptor (TNFR) genes are alternatively spliced in a regulated manner to produce either soluble or membrane-associated signal-transducing forms [10][11][12][13][14][15]. Xing et al [16] showed that alternative inclusion/exclusion of membrane-spanning regions is a common outcome of alternative splicing, a result that was corroborated in a mouse-specific study [17].…”
Section: Introductionmentioning
confidence: 99%
“…In general, preanalytic conditions are critical in the assessment of sCD40L concentrations. Some reports document the effects of specimen type (serum and Potential role of selected biomarkers for predicting the presence and extent of coronary artery disease 2 Statistical significance of differences in continuous variables between groups of patients was analysed by means of Mann -Whitney U test; α=0.05 was adopted as a level of significance for all tests and statistically significant results are given in bold and denoted by * 2 Statistical significance of differences in continuous variables between groups of patients was analysed by means of Mann -Whitney U test; α=0.05 was adopted as a level of significance for all tests and statistically significant results are given in bold and denoted by * MMP-3, matrix-metalloproteinase-3; CAD, coronary artery disease 1 Statistical significance was analysed by means of ML Chi-square test; α=0.05 was adopted as a level of significance for all tests and statistically significant results are given in bold and denoted plasma), processing (time and temperature), and commercial reagent selection on sCD40L ELISA results 27,28 . High-sensitivity ELISA assay suitable for plasma and serum testing (Bender MedSystems) was used.…”
Section: Discussionmentioning
confidence: 99%
“…The results can in part be affected by specimen type: in our study blood serum was tested. As for Halldorsdottir et al the optimum strategy would be to measure sCD40L in platelet-free plasma 28 . Variability in statin administration could play its role as well (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Other members of the TNF receptor family and several cytokine receptors that are found as soluble receptors are generated by alternative splicing (28)(29)(30)(31). We recently identified a biologically active soluble TNF-a receptor 2 isoform (DS-TNFR2) that was generated by alternative splicing and that antagonised TNF-a action in in vivo studies (32).…”
Section: Introductionmentioning
confidence: 99%
“…DS-TNFR2 was present in the serum of healthy individuals (32). We aimed to a) confirm the existence of DS-TNFR2 mRNA in peripheral monocytes from healthy subjects; and b) to evaluate circulating DS-TNFR2 in association with insulin action in vivo.…”
Section: Introductionmentioning
confidence: 99%